Effect of Patient-Reported Preprocedural Physical and Mental Health on 10-Year Mortality After Percutaneous or Surgical Coronary Revascularization. Issue 17 (18th July 2022) - Ono, Masafumi; Serruys, Patrick W.; Garg, Scot; Kawashima, Hideyuki; Gao, Chao; Hara, Hironori; Lunardi, Mattia; Wang, Rutao; O'Leary, Neil; Wykrzykowska, Joanna J.; Piek, Jan J.; Mack, Michael J.; et al.
Abstract : Background: Clinical and anatomical characteristics are often considered key factors in deciding between percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) in patients with complex coronary artery disease (CAD) such as left-main CAD or 3-vessel disease. However, little is known about the interaction between self-reported preprocedural physical/mental health and clinical outcomes after revascularization. Methods: This subgroup analysis of the SYNTAXES trial (SYNTAX Extended Survival), which is the extended follow-up of the randomized SYNTAX trial (Synergy Between PCI With Taxus and Cardiac Surgery) comparing PCI with CABG in patients with left-main CAD or 3-vessel disease, stratified patients by terciles of Physical (PCS) or Mental Component Summary (MCS) scores derived from the preprocedural 36-Item Short Form Health Survey, with higher PCS and MCS scores representing better physical and mental health, respectively. The primary end point was all-cause death at 10 years. Results: A total of 1656 patients with preprocedural 36-Item Short Form Health Survey data were included in the present study. Both higher PCS and MCS were independently associated with lower 10-year mortality (10-point increase in PCS adjusted hazard ratio, 0.84 [95% CI, 0.73–0.97]; P =0.021; in MCS adjusted hazard ratio, 0.85 [95% CI, 0.76–0.95]; P =0.005). A significant survival benefit with CABG over PCI was observed in the highest PCS (>45.5) and MCS (>52.3) terciles with significant treatment-by-subgroup interactions (PCS P interaction =0.033, MCS P interaction =0.015). In patients with both high PCS (>45.5) and MCS (>52.3), 10-year mortality was significantly higher with PCI compared with CABG (30.5% versus 12.2%; hazard ratio, 2.87 [95% CI, 1.55–5.30]; P =0.001), whereas among those with low PCS (≤45.5) or low MCS (≤52.3), there were no significant differences in 10-year mortality between PCI and CABG, resulting in a significant treatment-by-subgroup interaction ( P interaction =0.002). Conclusions: Among patients with left-main CAD or 3-vessel disease, patient-reported preprocedural physical and mental health status was strongly associated with long-term mortality and modified the relative treatment effects of PCI versus CABG. Patients with the best physical and mental health had better 10-year survival with CABG compared with PCI. Assessment of self-reported physical and mental health is important when selecting the optimal revascularization strategy. Registration: URL: https://www.clinicaltrials.gov ; SYNTAXES Unique identifier: NCT03417050. URL: https://www.clinicaltrials.gov ; SYNTAX Unique identifier: NCT00114972.